NON-PARTICIPATION OF HIGH SCHOOL STUDENTS INPHYSICAL EDUCATION CLASSES (Fiep Bulletin - online, 2013)
This article presents some of the key aspects that influence the non-participation of students in Physical Education classes in high school, reflected through the perception of the actors in this process. The theoretical principles feature Physical Education in high school, exposing cutouts of legislation that regulate the inclusion of this subject in basic education and discuss the prospects of a curriculum for this area, bringing the perception of some authors about the lack of motivation participation in the Physical Education activities. The study has a qualitative character and used as are search instrument, a semi-structured questionnaire, applied to students who do not usually participate in physical education classes in schools of two counties in Região do Médio Alto Uruguai, in the state of Rio Grande do Sul. Through content analysis, the data collected outline categories of analysis that reflect the class methodology and content, the planning and evaluation of activities, incentive and motivation of both teachers and students, interpersonal relationships and appreciation for this subject in the educational space. From the exposed reflections it is possible to point out that the non-participation in class is due to students lack of motivation concerning repetitive sport-related contents de contextualized from their perspectives; lack of planning and evaluation of diversified activities; teacher´s unawareness about the lack of motivation in the classes and the need for professional interventions that value and legitimize this area of ??knowledge in school.
Keywords: Physical Education; motivation; non-participation.